SAT0174 Efficacy of Sarilumab plus csDMARDs in Rheumatoid Arthritis Patients Who Had An Inadequate Response To One or More than One Prior TNF Inhibitor. (15th July 2016) - Genovese, M.C.; Pinheiro, G.da R.C.; Mangan, E.K.; Lin, Y.; van Adelsberg, J.; van Hoogstraten, H.; Thompson, D.; Fleischmann, R.
Abstract : Background: In the phase 3 TARGET study (NCT01709578 ), sarilumab (150 or 200 mg subcutaneously [SC] every 2 weeks [q2w] plus conventional synthetic disease-modifying antirheumatic drugs [csDMARDs]) demonstrated efficacy in adults with active, moderate-to-severe rheumatoid arthritis (RA) and inadequate response to tumor necrosis factor inhibitors (TNFis). 1 Consistent with IL-6 inhibition and the safety profile of SC sarilumab, infections, neutropenia, injection site reactions, increased lipids, and increased transaminases were among the most common treatment-emergent adverse events. Objectives: This prespecified analysis examined whether the efficacy of sarilumab plus csDMARDs was affected by the number of prior TNFis. Methods: Adults with active, moderate-to-severe RA with inadequate response or intolerance to ≥1 TNFi were randomized to receive placebo (n=181), sarilumab 150 mg q2w (n=181), or sarilumab 200 mg q2w (n=184) SC plus csDMARD(s) for 24 weeks. 1 Efficacy by number of prior TNFis (1 vs >1) was analyzed for the coprimary endpoints of ACR20 response at week 24 and mean change from baseline in Health Assessment Questionnaire–Disability Index (HAQ-DI) at week 12. Additional post hoc analyses evaluated the secondary endpoints of ACR50/70. Treatment-by-subgroup interactions were analyzed using a logistic regression model for ACR20 at week 24 and a mixed-effect model for repeated measures for HAQ-DI at week 12; treatment-by-subgroup interaction with P <0.05 was considered significant. Results: A majority of patients (76.8%) reported prior use of only 1 TNFi; 23.2% of patients used >1 TNFi. Most patients discontinued TNFi treatment because of inadequate response (92.3%). ACR20 responses were numerically greater in patients receiving either dose of sarilumab in both the 1 and the >1 prior TNFi groups at week 24 relative to placebo patients (Table ). Responses in placebo and sarilumab groups were numerically higher in the group that failed 1 TNFi. Similar results were observed with ACR50/70 responses. The mean change from baseline in HAQ-DI at week 12 was greater in sarilumab patients than in placebo patients in both prior TNFi exposure groups. Interaction test analyses indicated no significant treatment-by-subgroup effect in the proportion of patients with 1 or >1 prior TNFi who achieved ACR20 at week 24 ( P =0.1215) or in mean change from baseline in HAQ-DI at week 12 ( P =0.1767). Conclusions: Efficacy of sarilumab was observed in patients with inadequate response to TNFis, irrespective of the number of prior TNFi therapies. In harder to treat patients (ie, patients with prior exposure to >1 TNFi), sarilumab 200 mg was associated with a greater numerical trend in ACR20/50 when compared with sarilumab 150 mg. References: Fleischmann et al. Presented at: ACR; Nov. 7–11, 2015; San Francisco, CA. Acknowledgement: This study was sponsored by Sanofi and Regeneron Pharmaceuticals, Inc. Editorial support was provided by Kristi Porter, PhD, MedThink SciCom, and funded by Sanofi and Regeneron Pharmaceuticals, Inc. Disclosure of Interest: M. Genovese Grant/research support from: BMS, GSK, R-Pharma, Roche, RuiYi, and Sanofi, Consultant for: BMS, GSK, R-Pharma, Roche, RuiYi, and Sanofi, G. da R.C. Pinheiro Consultant for: AbbVie, AstraZeneca, GlaxoSmithKline, Hospira, Janssen, Pfizer, Roche, RuiYi, and Sanofi, E. Mangan Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, Y. Lin Shareholder of: Sanofi, Employee of: Sanofi, J. van Adelsberg Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, H. van Hoogstraten Shareholder of: Sanofi, Employee of: Sanofi, D. Thompson Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, R. Fleischmann Grant/research support from: AbbVie, Amgen, Ardea, AstraZeneca, BMS, Celgene, Eli Lilly, GSK, Janssen, Merck, Pfizer, Roche, Sanofi, and UCB, Consultant for: AbbVie, Akros, Amgen, AstraZeneca, BMS, Eli Lilly, Janssen, Pfizer, Roche, and UCB